Compositional analysis and nutritional profiling of Southeast Asian fermented fish products: Insights into macronutrients, micronutrients, and bioactive compounds - Norliza Julmohammad; Mazlinah Atun; Jumardi Roslan; Amir Husni Mohd Shariff; Frederick Adzitey; Sukoso; Nurul Huda (Springer Nature, 2025)
This study evaluated the nutritional quality of Traditional Southeast Asian fermented fish products, such as fish sauces (Budu, Nampla,) and shrimp pastes (Bagoong Alamang, Kapi, Belacan, Terasi) through proximate analysis, mineral content evaluation, fatty acid profiling, and amino acid composition assessment. Shrimp pastes exhibited higher protein and fat content compared to fish sauces. Fish sauces had higher sodium (4.45 mg/l) and calcium (14.46 mg/l) levels, while shrimp pastes had elevated mineral contents, including potassium (706.61 mg/l), magnesium (351.43 mg/l), and phosphorus (621.06 mg/l). Fatty acid analysis revealed that Terasi had the highest alpha-linolenic acid (ALA) (2.9%) and Belacan had the highest linoleic acid (LA) (5.3%). Amino acid analysis revealed that Terasi was rich in essential amino acid content and higher chemical and amino acid scores, indicating a high-quality protein source. The results highlight that traditional Southeast Asian shrimp pastes offer higher nutritional benefits in terms of protein, fat, and minerals compared to fish sauces.